Succinic acid production from duckweed (Landoltia punctata) hydrolysate by batch fermentation of Actinobacillus succinogenes GXAS137. (July 2016) - Shen, Naikun; Wang, Qingyan; Zhu, Jing; Qin, Yan; Liao, Siming; Li, Yi; Zhu, Qixia; Jin, Yanling; Du, Liqin; Huang, Ribo
Highlights: A cost-effective method of producing succinic acid form duckweed was created. Acid hydrolysis was a more effective method due to the higher succinic acid yield. CSLP was used as nitrogen source to replace YE for succinic acid production. The succinic acid concentration reached to 57.8 g/L at 64.4 g/L total sugar loading. Abstract: Duckweed is potentially an ideal succinic acid (SA) feedstock due to its high proportion of starch and low lignin content. Pretreatment methods, substrate content and nitrogen source were investigated to enhance the bioconversion of duckweed to SA and to reduce the costs of production. Results showed that acid hydrolysis was an effective pretreatment method because of its high SA yield. The optimum substrate concentration was 140 g/L. The optimum substrate concentration was 140 g/L. Corn steep liquor powder could be considered a feasible and inexpensive alternative to yeast extract as a nitrogen source. Approximately 57.85 g/L of SA was produced when batch fermentation was conducted in a 1.3 L stirred bioreactor. Therefore, inexpensive duckweed can be a promising feedstock for the economical and efficient production of SA through fermentation by Actinobacillus succinogenes GXAS137.